2016
DOI: 10.1021/acs.jpca.5b12273
|View full text |Cite
|
Sign up to set email alerts
|

Product Channels in the Reaction of the Hydroxymethyl Radical with Nitric Oxide

Abstract: The products of the reaction of CH2OH with NO were studied by infrared diode laser spectroscopy. Products were detected to determine the branching ratios of the CH2OH + NO reaction. HNCO was detected in 10.3 ± 2% yields. No other products were detected in significant quantities, indicating that adduct formation is the primary reaction pathway. Ab initio calculations of the potential energy surface show a low energy pathway to HNCO + H2O, but no other bimolecular channels, in agreement with the experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Of these two products, methyl nitrite (CH 3 ONO) was clearly detected via FTIR (Section ), and PI-ReTOF-MS (Section ) as the main irradiation product. As for the nitrosomethanol (HOCH 2 NO) isomer, gas-phase experimental and theoretical studies suggested the formation of the transient “HOCH 2 NO adduct” as a result of the reaction of hydroxymethyl (CH 2 OH) radicals with nitrogen monoxide (NO). A recent infrared diode laser spectroscopy study combined with ab initio calculations was also performed on the reaction hydroxymethyl (CH 2 OH) and nitrogen monoxide (NO) in the gas phase . It has been pointed out that the formed intermediate nitrosomethanol (HOCH 2 NO) adduct may eventually decompose to isocyanic acid (HNCO) and water (H 2 O), although at a rather moderate yield of 10 ± 2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these two products, methyl nitrite (CH 3 ONO) was clearly detected via FTIR (Section ), and PI-ReTOF-MS (Section ) as the main irradiation product. As for the nitrosomethanol (HOCH 2 NO) isomer, gas-phase experimental and theoretical studies suggested the formation of the transient “HOCH 2 NO adduct” as a result of the reaction of hydroxymethyl (CH 2 OH) radicals with nitrogen monoxide (NO). A recent infrared diode laser spectroscopy study combined with ab initio calculations was also performed on the reaction hydroxymethyl (CH 2 OH) and nitrogen monoxide (NO) in the gas phase . It has been pointed out that the formed intermediate nitrosomethanol (HOCH 2 NO) adduct may eventually decompose to isocyanic acid (HNCO) and water (H 2 O), although at a rather moderate yield of 10 ± 2%.…”
Section: Discussionmentioning
confidence: 99%
“…57−59 A recent infrared diode laser spectroscopy study combined with ab initio calculations was also performed on the reaction hydroxymethyl (CH 2 OH) and nitrogen monoxide (NO) in the gas phase. 60 It has been pointed out that the formed intermediate nitrosomethanol (HOCH 2 NO) adduct may eventually decompose to isocyanic acid (HNCO) and water (H 2 O), although at a rather moderate yield of 10 ± 2%. Most importantly, even though the adduct formation pathway was concluded to be the main one, the authors were unable to detect the collisionally stabilized nitrosomethanol (HOCH 2 NO) molecule.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 99%